A new 5D fractional-order conservative hyperchaos system. (1st January 2023) - Tian, Bowen; Peng, Qiqi; Leng, Xiangxin; Du, Baoxiang
Abstract: At present, most of the encryption algorithms based on chaotic systems use dissipative chaotic systems. However, the dissipative chaotic systems have attractors and are easy to reconstruct, which leads to potential security risks in the process of data transmission. Therefore, a novel five-dimensional conservative hyperchaotic system is proposed in this paper, and the integer order system is transformed into a fractional-order system based on the Adomian decomposition method(ADM). The dynamic characteristics of the system are discussed by using classical analysis methods such as Lyapunov exponent spectrum(LEs), bifurcation diagram, phase diagram, and timing diagram. By changing the system parameters and the differential order q, we found a wealth of dynamic phenomena, such as quasi-periodic flow, chaotic flow, and hyperchaotic flow. When the initial value is used as a variable, it is found that the system has initial offset boosting behavior, multiple stability, and special transient behavior. In addition, we use the spectral entropy algorithm to analyze the complexity of the system. Finally, hardware experiments are also carried out using digital signal processor (DSP) to verify the correctness of the numerical simulation, and also to prove the physical realizability of the system, to create conditions for its subsequent engineering applications.